2022
DOI: 10.1007/s00415-022-11309-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delirium on the outcome of stroke: a prospective, observational, cohort study

Abstract: Introduction Delirium is an acute fluctuating disorder of attention and awareness, which often complicates the clinical course of several conditions, including acute stroke. The aim of the present study was to determine whether delirium occurrence impacts the outcome of patients with acute stroke. Methods The study design is single center, prospective, observational. We consecutively enrolled patients admitted to the stroke unit from April to October 2020.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…This study found that the prevalence of insomnia using the Insomnia Assessment Diagnostic Tool was 51.16%, which was higher than the prevalence of self-reported insomnia (37.58%). In contrast, in study using the insomnia assessment and diagnostic tool, the prevalence of insomnia was different in acute phase and subacute phase stroke (32.5% vs 34.8%), whereas the overall prevalence of self-assessed insomnia also was different in acute phase and subacute phase stroke (47.1% vs 50.4%) [ 52 ]. Further large-sample studies are needed to validate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the prevalence of insomnia using the Insomnia Assessment Diagnostic Tool was 51.16%, which was higher than the prevalence of self-reported insomnia (37.58%). In contrast, in study using the insomnia assessment and diagnostic tool, the prevalence of insomnia was different in acute phase and subacute phase stroke (32.5% vs 34.8%), whereas the overall prevalence of self-assessed insomnia also was different in acute phase and subacute phase stroke (47.1% vs 50.4%) [ 52 ]. Further large-sample studies are needed to validate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Shi et al in 2012 summarized in their meta-analysis that post-stroke delirium was associated with higher one-year mortality [ 37 ], and these results have also been confirmed by subsequent authors [ 38 , 39 ]. Although the negative impact of post-stroke delirium on functional disability is known [ 38 , 40 ], long-term data were still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating self-reported insomnia symptoms by means of questionnaires, the summary prevalence was 47.1% in the acute phase, and 50.4% in the subacute phase [1••]. However, it is worth to consider that insomnia is a multifactorial disorder, where a big contribution to sleep disruption is played by the hospital setting; importantly, sleep fragmentation in acute stroke is associated with an increased risk for stroke-associated delirium [112] that is, in turn, associated to poorer long-term outcome [113]. Nonetheless, studies in which insomnia was evaluated at different time points, up to 18 months from stroke onset, revealed a prevalence of insomnia symptoms near to 50% [114,115].…”
Section: Stroke Recovery and Outcomementioning
confidence: 99%